Question and answer
x + y = 6 2x - y = 3 The system of equations
x + y = 6 2x - y = 3 y = -x + 6 2x - (-x + 6) = 3 2x + x - 6 = 3 3x - 6 = 3 3x = 3 + 6 3x = 9 x = 9/3 x = 3 3 + y = 6 y = 6 - 3 y = 3 Solution set: x = 3, y = 3
Question
Asked 1/5/2018 1:16:35 PM
Updated 1/5/2018 6:22:50 PM
1 Answer/Comment
Edited by Masamune [1/5/2018 6:22:41 PM]
Get an answer
New answers
Rating
3
x + y = 6
2x - y = 3

y = -x + 6
2x - (-x + 6) = 3
2x + x - 6 = 3
3x - 6 = 3
3x = 3 + 6
3x = 9
x = 9/3
x = 3

3 + y = 6
y = 6 - 3
y = 3

Solution set: x = 3, y = 3
Added 1/5/2018 6:22:50 PM
This answer has been confirmed as correct and helpful.
Comments

There are no comments.

Add an answer or comment
Log in or sign up first.
29,733,014
questions answered
*
Get answers from Weegy and a team of really smart live experts.
S
L
R
R
Points 1686 [Total 3201] Ratings 8 Comments 336 Invitations 127 Online
S
L
Points 1176 [Total 1176] Ratings 6 Comments 1096 Invitations 2 Offline
S
L
P
C
P
C
P
C
Points 1143 [Total 4939] Ratings 5 Comments 1093 Invitations 0 Offline
S
L
R
Points 1041 [Total 1678] Ratings 9 Comments 371 Invitations 58 Online
S
L
Points 635 [Total 1075] Ratings 3 Comments 585 Invitations 2 Offline
S
L
Points 520 [Total 2637] Ratings 5 Comments 470 Invitations 0 Offline
S
L
1
P
1
Points 338 [Total 1787] Ratings 11 Comments 228 Invitations 0 Offline
S
L
Points 176 [Total 669] Ratings 4 Comments 116 Invitations 2 Offline
S
L
Points 157 [Total 608] Ratings 1 Comments 147 Invitations 0 Offline
S
L
Points 147 [Total 157] Ratings 0 Comments 137 Invitations 1 Offline
* Excludes moderators and previous
winners (Include)
Home | Contact | Blog | About | Terms | Privacy | © Purple Inc.